Expectations and Understanding of Learning in Practice: Student Speech and Language Therapists’ and Practice Educators’ Perspectives of Learning - Davies, Karen Elizabeth; Kevan, Fiona; Ormerod, Emma (International Journal of Practice-based Learning in Health and Social Care, 2019)
Research in speech and language therapy education has focussed on investigating models of clinical placements, rather than how learning is optimised in practical settings. A distinction has been made in practice-based learning in medical education between ‘capability’ and ‘competency’, urging educators to prioritise learning that enables problem solving and application of theory. We know little about student speech and language therapists’ (SLTs) and educators’ perception and expectations of clinical learning in placement and how this relates to capability. We investigated student SLTs’ and educators’ beliefs and experiences of successful learning in clinical settings and how they perceived their learner/educator roles using a qualitative study. Data was gathered from 28 students and educators using individual interviews and focus groups. The data was investigated using thematic analysis. Educators see their role as facilitators, developing core skills such as clinical reasoning, understanding professional identity and gaining independence. Some educators see this as a co-learning model, creating opportunities for their own learning. Students’ conceptions change during clinical placements, from focussing on their own development to seeking to understand the client’s perspective as well as identify needs, and respond with well-reasoned options for intervention. Aiming to equip SLT learners to be capable professionals, able to apply skills of clinical reasoning, is considered a core skill for SLT educators. Developing models for clinical placements informed by understanding how students learn to become capable could enhance the readiness of student SLTs to enter professional practice.